A survey of partial differential equations with piecewise continuous arguments - Joseph Wiener; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
Some work is described and new topics are posed on initial and boundary-value problems for partial differential equations whose arguments have intervals of constancy. These equations are of considerable theoretical and applied interest.